Clinical and laboratory characteristics of the patterns of chronic kidney disease in patients with type 2 diabetes - Vadim V. Klimontov; Anton I. Korbut; Olga N. Fazullina; Ilya V. Vinogradov; Vyacheslav V. Romanov (Сахарный диабет)
BACKGROUND: A growing body of evidence demonstrates increasing prevalence of normoalbuminuric chronic kidney disease (NA-CKD) in subjects with type 2 diabetes (T2D), while proportion of albuminuric pattern is decreasing. AIMS: To determine the clinical and laboratory parameters associated with different patterns of CKD in patients with T2D. METHODS: This observational, single-center, cross-sectional study included 360 patients with T2D duration ≥10 years. Patients with urinary albumin/creatinine ratio (UACR) <3 mg/mmol and estimated glomerular filtration rate (eGFR) >60 ml/min/1.73 m2 were classified as no-CKD group (n=89). Patients with UACR <3 mg/mmol and eGFR <60 ml/min/1.73 m2 formed NA-CKD group (n=111). Individuals with eGFR ≥60 ml/min/1.73 m2 and UACR mg/mmol ≥3 were recorded as albuminuric with preserved renal function (A-CKD–, n=87). Patients with eGFR <60 ml/min/1.73 m2 and UACR mg/mmol ≥3 mg/mmol were considered as albuminuric CKD group (A-CKD+, n=73). Urinary nephrin and podocin, the podocyte injury markers, and whey acidic protein four-disulfide core domain protein 2 (WFDC-2), a marker of tubulointerstitial involvement, was assessed by ELISA and compared to control (20 non-diabetic subjects). RESULTS: Age ≥65 years (p=0.0001), duration of T2D ≥15 years (p=0.0009), female sex (p=0.04), and therapy with diuretics (p=0.0005) were found as risk factors for NA-CKD. The risk factors for A-CKD were male sex (p=0.01), smoking (p=0.01), waist-to-hip ratio >1 (p=0.01) and HbA1c levels >8% (p=0.005). The duration of T2D ≥15 years (p=0.01) and the use of dihydropyridine calcium channel blockers (p=0.01) were associated with A-CKD+. In T2D groups, the urinary excretion of nephrin and podocin was increased (all p<0.001), more markedly in albuminuric individuals (p<0.01 vs. NA-CKD). WFDC-2 excretion was increased in men from all diabetic groups (p<0.05) and in women with decreased eGFR only (p<0.05 vs. the control and NA-CKD). CONCLUSIONS: The CKD patterns in T2D are heterogeneous according to their clinical and laboratory characteristics. The changes in the excretion of nephrin and podocin indicate the association of albuminuric patterns with podocyte injury. A decrease in eGFR in women with T2D is associated with an increase in urinary excretion of WFDC-2, tubulointerstitial fibrosis marker.